Glucose Injection Into Yolk Positively Modulates Intermediary Metabolism and Growth Performance in Juvenile Nile Tilapia (Oreochromis niloticus) - Kumkhong, Suksan; Marandel, Lucie; Plagnes-Juan, Elisabeth; Veron, Vincent; Boonanuntanasarn, Surintorn; Panserat, Stephane (Frontiers in Physiology, 2020)
The aim of this study was to explore for the first time in omnivorous fish the concept of nutritional programming. A nutritional stimulus was accomplished by micro-injecting 2 M glucose into yolk reserves during the alevin stage in Nile tilapia (Oreochromis niloticus). At the molecular level in fry, at one week post-injection, glucose stimuli were associated with the up-regulation of genes involved in glycolysis (pklr, hk1, hk2 and pkma), glucose transport (glut4) pathways and down-regulation of genes related to gluconeogenesis (g6pca1, g6pca2 and pck1) and amino acid catabolism (asat, alat) (P<0.05), demonstrating that the larvae well received the glucose stimulus at a molecular level. Moreover, 20 weeks after glucose injection, early glucose stimuli were always linked to permanent effects in juvenile fish, as reflected by a higher level of glycolytic enzymes (gck, hk1 and hk2 at both mRNA and enzymatic levels and pyruvate kinase [PK] activity). Finally, the effects of the glucose stimulus history were also examined in fish fed with two different dietary carbohydrate/protein levels (medium-carbohydrate diet, CHO-M; high-carbohydrate diet, CHO-H) in juvenile fish (during weeks 20–24). As expected, the CHO-H diet induced the expression of glycolytic and lipogenic genes (gck, pklr, hk1, hk2, fpkma, fasn and g6pd) and suppressed the expression of gluconeogenic and amino acid catabolism genes (g6pca1, pck1, pck2, asat, alat and gdh). Nevertheless, the early glucose stimulus led to persistent up-regulation of glycolytic enzymes (gck, pklr, hk1 and hk2) at both the mRNA and enzyme activity levels and glucose transporter glut4 as well as lower gluconeogenic pck1 gene expression (P<0.05). More interestingly, the early glucose stimulus was associated with a better growth performance of juvenile fish irrespective of the diets. These permanent changes were associated with DNA hypomethylation in the liver and muscles, suggesting the existence of epigenetic mechanisms at the origin of programming. In conclusion, for the first time in tilapia, early glucose stimuli were found to be clearly associated with a positive metabolic programming effect later in life, improving the growth performance of the fish.